The History of Ethical, Environmental, Social, and Governance-Oriented Investments as a Key to Sustainable Prosperity in the Finance World. (4th March 2019) - Puaschunder, Julia M.
Abstract : In recent decades Socially Responsible Investment (SRI) emerged into an en vogue investment strategy. Socially Responsible Investment (SRI) is an investment philosophy that combines profit maximization with social endeavors. By integrating social, environmental, and financial aspects in investments, socially conscientious investors pursue economic and social value maximization alike. Financial goals can be coupled with catalyzing sociopolitical change in various forms. Socially responsible screenings are "double bottom line analyses" of corporate economic performance and social responsibility, in which socially conscientious investors incorporate Corporate Social Responsibility (CSR) in financial decision making and allocate financial resources based on the societal impacts of the funded entities. Originating from religious and moral considerations, SRI evolved in the wake of sociopolitical deficiencies and corporate social conduct. In the global rise of financial social conscientiousness, differing national legislations and regulatory traditions have led to various SRI practices, which are harmonized by the United Nations (UN). Building on the historic advancement of Financial Social Responsibility in the wake of socioethical deficiencies, this article highlights the potential of SRI in the aftermath of the 2008/09 World Financial Crisis as a means to avert economic market downfalls. During the current financial market reform, additional micro- and macro-research on financial social conduct could foster the idea of Financial Social Responsibility and aid a successful implementation of SRI.